Micafungin Compared with Caspofungin for the Treatment of Febrile Episodes in Neutropenic Patients with Hematological Malignancies: A Retrospective Study - Sarah Shalhoub; Luchen Wang; Arthur Ching; Shahid Husain; Coleman Rotstein (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Invasive fungal infections are associated with morbidity and mortality in neutropenia secondary to hematological malignancies. Empirical antifungal agents are used to reduce their consequences. Caspofungin is the only echinocandin approved for this indication. Micafungin was compared with caspofungin for the treatment of patients with hematological malignancies and prolonged neutropenia.